Characteristics of Intellectual Production of Academic Journals at Tishreen University: A Bibliometric Study of the Journal of Arts and Humanities Series 2015 - - عيسى, سهير (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
scientific production has become one of the important topics because of its role in knowing the characteristics of published research and finding out the weaknesses in this production and trying to evaluate it . The study aims at analyzing the journal of literature and humanities issued by, journal of tishreen university, and identify the features of the journal's intellectual production since 2015 to 2023, it also aims at monitoring the numerical, qualitative. Objective and linguistic trends. In addition to the study of the author's productivity in the different majors covered by journal The study relied on bibliometric method , The number of articles covered in that period amounted to 1,687 article in 9 volumes spread over 54, Topping the topic of education in the journal at a higher rate estimated (26.20%), Among the most important results that joint authorship is more than the Solo author, and the number of periodicals cited in the articles reached 1,751 periodical, at a rate of 7,051 reference certificates, Where the Arab patrols received a greater number of reference citations by (61.70%), and Damascus University's is most cited journal 10.84%.